2021
DOI: 10.7759/cureus.13688
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Suspected Radiation Recall Pneumonitis After a COVID-19 Infection

Abstract: We present the case of a 78-year-old woman who received definitive radiation therapy for small cell lung cancer three and a half years ago. She was asymptomatic when she tested positive for coronavirus disease 2019 (COVID-19). She then developed a rapid decline in respiratory status on day seven. Chest radiograph revealed a strong shadow at the prior irradiation site. Radiation recall reactions are usually caused by drug administration, but in this case, it was suspected to be caused by COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
0
9
0
Order By: Relevance
“… 18 Moreover, Huges et al reported a case of vaccination-induced RRP diagnosed via an FDG-PET CT scan four days after receiving the second dose of the mRNA COVID-19 vaccine in a patient with lung adenocarcinoma who had undergone radiotherapy followed by chemotherapy and pembrolizumab eighteen months earlier. 35 A suspected case of RRP has also been reported by Kuroaski et al 20 Certain authors have described a suspected case of a 78-year-old woman who received definitive radiation therapy for small cell lung cancer three and a half years before the COVID-19 pandemic and developed a rapid decline in her respiratory status. She died but an autopsy was not performed.…”
Section: Discussionmentioning
confidence: 77%
“… 18 Moreover, Huges et al reported a case of vaccination-induced RRP diagnosed via an FDG-PET CT scan four days after receiving the second dose of the mRNA COVID-19 vaccine in a patient with lung adenocarcinoma who had undergone radiotherapy followed by chemotherapy and pembrolizumab eighteen months earlier. 35 A suspected case of RRP has also been reported by Kuroaski et al 20 Certain authors have described a suspected case of a 78-year-old woman who received definitive radiation therapy for small cell lung cancer three and a half years before the COVID-19 pandemic and developed a rapid decline in her respiratory status. She died but an autopsy was not performed.…”
Section: Discussionmentioning
confidence: 77%
“…A suspected case of RRP has been shown by Kuroaski et al [20]. Authors described a suspected case of a 78-year-old woman who had received de nitive radiation therapy for small cell lung cancer three and a half years before the Covid-19 infection, developing a rapid decline in respiratory status.…”
Section: Discussionmentioning
confidence: 98%
“…Among drugs, chemotherapy, antibiotics, antimetabolites, vaccines have been involved in this process [22]. Interestingly, in this pandemic time, this phenomenon has been reported after a antiCovid-19 vaccine administration and few cases have been described due to Covid-19 infection [18,19,20]. Even if skin is reported as the most involved site, RR has been detected in other organs such as lung, oesophagus, small intestine muscle, central nervous system, and head and neck, depending on variations in tissue tolerance and local repairing mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 virus itself may induce similar effects: Kurosaki et al, for instance, have reported an RRP pneumonitis coinciding with COVID-19 infection, 3.5 years after initial RT. 5 …”
mentioning
confidence: 99%